Improved Excitation Light Rejection Enhances Small-Animal Fluorescent Optical Imaging - Kildong Hwang; Jessica P. Houston; John C. Rasmussen; Amit Joshi; Shi Ke; Chun Li; Eva M. Sevick-Muraca (Molecular Imaging)
Small-animal fluorescence-enhanced imaging involves the detection of weak fluorescent signals emanating from nanomolar to picomolar concentrations of exogenous or endogenously produced fluorophore concurrent with the rejection of an overwhelmingly large component of backscattered excitation light. The elimination of the back-reflected excitation light of the collected signal remains a major and often unrecognized challenge for further reducing the noise floor and increasing sensitivity of small-animal fluorescence imaging. Herein, we show that the combination of three-cavity interference and holographic super notch filters with appropriate imaging lenses to collimate light improves rejection of excitation light, enabling more accurate imaging. To assess excitation leakage, the “out-of-band ( S (Λ x ))” to “in-band ( S (Λ m )– S (Λ x ))” signal ratio from phantom studies and the target-to-background ratio (TBR) from in vivo animal imaging was acquired with and without collimating optics. The addition of collimating optics resulted in a 51% to 75% reduction in the ratio of ( S (Λ x ))/( S (Λ m )– S (Λ x )) for the phantom studies and an improvement of TBR from 11% to 31% and of signal-to-noise ratio from 11% to 142% for an integrin-targeting conjugate in human glioma xenografts.